2021
DOI: 10.1155/2021/7799793
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fatigue Driving State Recognition and Warning Method Based on EEG and EOG Signals

Abstract: Traffic accidents are easily caused by tired driving. If the fatigue state of the driver can be identified in time and a corresponding early warning can be provided, then the occurrence of traffic accidents could be avoided to a large extent. At present, the recognition of fatigue driving states is mostly based on recognition accuracy. Fatigue state is currently recognized by combining different features, such as facial expressions, electroencephalogram (EEG) signals, yawning, and the percentage of eyelid clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Earlier, two characteristics of EEG signals i.e., power spectral density (PSD) and sample entropy (SampEn) were integrated to assess cognitive fatigueness [52]. Integration of EEG signals with other features including facial expressions, yawning, and the percentage of eyelid closure over the pupil over time (PERCLoS) were also implemented to determine a driver fatigue state [53].…”
Section: Driver Fatigue Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, two characteristics of EEG signals i.e., power spectral density (PSD) and sample entropy (SampEn) were integrated to assess cognitive fatigueness [52]. Integration of EEG signals with other features including facial expressions, yawning, and the percentage of eyelid closure over the pupil over time (PERCLoS) were also implemented to determine a driver fatigue state [53].…”
Section: Driver Fatigue Monitoringmentioning
confidence: 99%
“…In another work, a fast support vector machine (FSVM) algorithm based on EEG and EOG modal data was implemented to recognize symptoms of driver fatigueness. When a symptom is visible, the driver and nearby vehicles will be informed via IoT technology [53]. On the other hand, the EEG signals were first reduced using the Weighted Principal Component Analysis (WPCA) algorithm before applying SVM to detect fatigue driver.…”
Section: Driver Fatigue Monitoringmentioning
confidence: 99%
“…Additionally, Huang et al [ 26 ] demonstrated the feasibility of EEG as a real-time fatigue detection and alerting system by examining alpha and theta power. However, even though EEG is frequently used to detect fatigue, the conventional setup is unsuitable for use in flight-related operations due to, for instance, the lengthy preparation time and limited mobility of the attached cap and electrodes] [ 3 , 14 , 27–29 ]. Nevertheless, the technology is still evolving, and manufacturers are increasingly developing innovative solutions to make EEG less invasive and more mobile [ 3 , 5 , 28 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kashani et al [13] have presented a framework based on data mining where tree is constructed towards performing classification and regression for investigating the prime indicators of fatigued-based accidents. Liu et al [14] have developed a solution model by combining two different physiological attributes related to signals of heart and eye blinks in order to recognize the fatigued state of driver. Model constructed by Zhao et al [15] have contributed towards detecting the level of distraction among the driver on the basis of estimated head poses of driver.…”
Section: Introductionmentioning
confidence: 99%